Geometric Morphometric Description of the Body Shapes of the "Porang" Fish, Rasbora Sp., an Endemic Fish Species in Lake Wood, Zamboanga Del Sur, Mindanao, Philippines (Journal of Informatics and Mathematical Sciences, 2017)
Biological descriptions of body shapes in fishes were commonly based on qualitative methods. However, with advances in imaging, geometry and statistics, descriptions of biological shapes have become more quantitative. Landmark-based geometric analysis is a new approach that has become more popular in analysing biological shapes thus was used in this study of an endemic fish species that can be found in a lake in Mindanao, Philippines. A total of 47 females and 104 male fishes were collected and digitized using 20 anatomical landmarks of the fish body. The digitized landmarks were Procrustes-fitted and were subjected to relative warp analysis (RWA). Relative warp scores were also subjected to Canonical Variate Analysis (CVA). RWA revealed within and between sex variations in body shapes. Male fish head is shorter and broader resulting to shorter length of the mouth from the snout tip to the posterior extremity of the premaxillar. Deeper body depth has also been viewed resulting to shorter standard length and longer and narrower tail region, while females have broader and elongated head regions having lengthy eye margins, extensive length between posterior insertion of anal fin and ventral points of the maximum curvature of the peduncle and mouth part are observed to have elongated distance between the snout tip and the posterior extremity of the premaxilla. These variations in shapes were observed in the two sexes, statistical analysis also has demonstrated that the shape variance between sexes in both left and right orientation of the body were significant. This means that the variations observed within sexes are sufficient to explain that the variations are associated to sex. Other characters aside from body shapes maybe are associated with sexual differences and should be further explored.
Keywords: Landmark-based geometric analysis; Endemic fish; Body shape; Relative warp scores; Canonical variate analysis